Transmitting Renewable Energy to the Grid : The Case of Texas - Madrigal, Marcelino (World Bank, Washington, DC, 2014)
The note is based on original work by Marcelino Madrigal and Steven Stoft, "Transmission Expansion for Renewable Energy Scale-Up: Emerging Lessons and Recommendations". Texas leads the United States with 9,528 MW of installed wind power capacity, a level exceeded by only four countries. The state needed more infrastructure to transmit electricity generated from renewable sources, but the regulator could not approve transmission expansion projects in the absence of financially committed generators. To solve the problem, Texas devised a planning process that quickly connects energy systems to the transmission system. The system is based on the designation of competitive renewable energy zones.